Foreign Objects in Colonial-Era Hawaiian Sites: Change and Continuity in Nineteenth-Century Nu‘alolo Kai, Kaua‘i Island - Moore, Summer (Waka Kuaka, 2020)
Archaeologists in Hawaiʻi, and Polynesia generally, have often struggled to exploit the interpretive potential of foreign artefacts in indigenous settings. This paper considers a consequential foreign artefact assemblage from Nuʻalolo Kai, a remote area on the Nā Pali Coast of Kaua‘i Island, Hawaiʻi. This archaeological assemblage derives from deeply stratified, well-preserved deposits that were excavated by Bishop Museum staff between 1958 and 1964. While these excavations were aimed at identifying early settlement sites on Kauaʻi, numerous foreign artefacts dating from the nineteenth century were also encountered. This article considers how these foreign materials can be used to refine the chronology of site use in the post-contact period and to gain a more robust picture of the Nuʻalolo Kai community during this important period of socioeconomic change. The analysis demonstrates that the boundary between pre-contact and “post-contact” lifeways, as represented in archaeological sites in Hawaiʻi and elsewhere in Polynesia, may be blurred. Moreover, the arrival of foreign goods did not have an immediate and “fatal impact” on traditional Hawaiian ways of life but instead denote cultural continuity, innovation and change. Finally, it is argued that trajectories of change in the household assemblages of rural nineteenth-century Hawaiʻi may have varied considerably from those seen in more connected areas of the archipelago.